THE EFFECT OF E-SERVICE QUALITY AND E-TRUST ON E-LOYALTY THROUGH E-SATISFACTION AS AN INTERVENING VARIABLE (Study on ShopeeFood customers) - Syifaul Linas Salwa; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (STKIP Singkawang, 2022)
This study aims to determine whether there is an effect of e-service quality and e-trust on e-loyalty through e-satisfaction as an intervening variable for ShopeeFood customers. The population used in this study were ShopeeFood customers in the city of Yogyakarta. This study uses a type of questionnaire that uses Google Form as a research tool. The research method used is non-probability sampling technique with purposive sampling method. The sample used is 100 respondents. The data obtained from the questionnaire was then processed and analyzed using Multiple Linear Regression analysis with model accuracy (classical assumption test), hypothesis testing using partial test (t) and determination test (R2) using SPSS 25 program. The results of this study indicate that e -service quality has a positive and significant effect on e-satisfaction, e-trust has a positive and significant effect on e-satisfaction, e-service quality has no significant effect on e-loualty, e-trust has no significant effect on e-loyalty, e-satisfaction has a positive and significant effect on e-loyalty, e-satisfaction has a positive and significant effect as an intervening variable, the effect of e-service quality on e-loyalty, and e-satisfaction has no significant effect as an intervening variable, the effect of e-trust on e-loyalty.